2016 21st Asia and South Pacific Design Automation Conference (ASP-DAC) 2016
DOI: 10.1109/aspdac.2016.7428061
|View full text |Cite
|
Sign up to set email alerts
|

Majority-based synthesis for nanotechnologies

Abstract: Abstract-We study the logic synthesis of emerging nanotechnologies whose elementary devices abstraction is a majority voter. We argue that synthesis tools, natively supporting the majority logic abstraction, are the technology enablers. This is because they allow designers to validate majority-based nanotechnologies on large-scale benchmarks. We describe models and datastructures for logic design with majority-based nanotechnologies and we show results of applying new synthesis algorithms and tools. We conclud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Recent research [10]- [13] has confirmed that majority logic can implement arithmetic-intensive circuits with fewer gates, and it has been proved that Majority-based logic can achieve up to 33% reduction in logical depth compared to And-based logic [13]. For example, when comparing with IMPLY, the computation efficiency of the mathematical addition doubles with the majority logic, which is one particular case of the threshold logic [14].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research [10]- [13] has confirmed that majority logic can implement arithmetic-intensive circuits with fewer gates, and it has been proved that Majority-based logic can achieve up to 33% reduction in logical depth compared to And-based logic [13]. For example, when comparing with IMPLY, the computation efficiency of the mathematical addition doubles with the majority logic, which is one particular case of the threshold logic [14].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, a majority gate is a democratic gate and can be expressed in terms of Boolean AND/OR as M AJ(a, b, c) = a • b + b • c + a • c, where a, b, c are Boolean variables. Although majority logic was known since 1960, there has been a revival in using it for computation in many emerging nanotechnologies (spin waves, magnetic Quantum-Dot cellular automata, nano magnetic logic, Single Electron Tunneling [21]- [23]). Recent research [22]- [25] has confirmed that majority logic is to be preferred not only because a particular nanotechnology can realize it, but also because of its ability to implement arithmetic-intensive circuits with less gates.…”
Section: Introductionmentioning
confidence: 99%
“…Although majority logic was known since 1960, there has been a rediscovery in using it for computation in many post-CMOS devices. A majority gate based on spin waves [7], Quantum-Dot cellular automata [8], nano magnetic logic [9], and Single Electron Tunneling [10] have been demonstrated and in some of these technologies, it is more efficient to implement a majority gate [11] than other other logic primitives (NAND, NOR, XOR). Recent research [6,[12][13][14] has confirmed that majority logic is to be preferred not only because a particular nanotechnology can realize it, but also because of its ability to implement arithmetic-intensive circuits with less gates, i.e., in a compact manner.…”
Section: Introductionmentioning
confidence: 99%